(untitled) (American Journal of Pedagogical and Educational Research, 2023)
These statistics on financial markets and interest rates reflect how prices, yields and volumes of financial instruments, as well as expectations about their future developments, vary over time. They facilitate analysis of the monetary policy transmission mechanism, in particular the extent and speed of the pass-through of changes in official rates to the credit market and the real economy as well as shifts between direct finance (through securities markets) and indirect finance (through the banking system). They are also essential for analysing financial stability and financial integration.